Срочно, писать не скорочено с повним обяснением
Срочно, писать не скорочено с повним обяснением
Ответ(ы) на вопрос:
Гость
[latex](n-\frac{5n-36}{n-7}):(2n+\frac{2n}{n-7})=\frac{n-6}{2n}[/latex] 1) [latex]n-\frac{5n-36}{n-7}=\frac{n(n-7)-(5n-36)}{n-7}=\frac{n^{2}-7n-5n+36}{n-7}= \frac{n^{2}+(-7n-5n)+36}{n-7}=\frac{n^{2}-12n+36}{n-7}=\frac{(n-6)(n-6)}{n-7}[/latex] 2) [latex]2n+\frac{2n}{n-7}=\frac{2n(n-7)+2n}{n-7}=\frac{2n^{2}-14n+2n}{n-7}=\frac{2n^{2}+(-14n+2n)}{n-7}=\frac{2n^{2}-12n)}{n-7}=\frac{2n(n-6)}{n-7}[/latex] 3) [latex]\frac{(n-6)(n-6)}{n-7}:\frac{2n(n-6)}{n-7}=\frac{(n-6)(n-6)}{n-7}\cdot\frac{n-7}{2n(n-6)}= \frac{(n-6)\cdot(n-6)\cdot(n-7)}{2n\cdot(n-7)\cdot(n-6)}=\frac{n-6}{2n} [/latex] [latex]\frac{n-6}{2n}=\frac{n-6}{2n}[/latex]
Не нашли ответ?
Похожие вопросы